2009
DOI: 10.1111/j.1365-3024.2008.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of immune epitope data for all Plasmodia: overview and applications for malarial immunobiology and vaccine‐related issues

Abstract: Summary We present a comprehensive meta-analysis of more than 500 references, describing nearly 5000 unique B cell and T cell epitopes derived from the Plasmodium genus, and detailing thousands of immunological assays. This is the first inventory of epitope data related to malaria-specific immunology, plasmodial pathogenesis, and vaccine performance. The survey included host and pathogen species distribution of epitopes, the number of antibody vs. CD4+ and CD8+ T cell epitopes, the genomic distribution of reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…Hitherto the sequences of approximately 5300 proteins were annotated for Plasmodium falciparum genome . Among them, there were identified about 4500 unique epitopes (present in about 1500 proteins), which are short protein motifs recognized by the host immune system (Vaughan et al, 2009 These results shows that comparison between currently existing diversity and genome of P. reichenovi may reveal immune pressure acting on pathogen after the speciation.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Hitherto the sequences of approximately 5300 proteins were annotated for Plasmodium falciparum genome . Among them, there were identified about 4500 unique epitopes (present in about 1500 proteins), which are short protein motifs recognized by the host immune system (Vaughan et al, 2009 These results shows that comparison between currently existing diversity and genome of P. reichenovi may reveal immune pressure acting on pathogen after the speciation.…”
Section: Introductionmentioning
confidence: 86%
“…Due to the complexity of the life cycle, each life stage expresses a number of antigenic proteins that can induce an immune response and which presents a real challenge for vaccine design (Vaughan et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses have been conducted for several highprofile pathogens, such as influenza A virus, mycobacteria (M. tuberculosis and related species), anthrax, and botulinum toxins, and all Plasmodium species (8,11,101,112). These analyses have provided comprehensive catalogs of pathogenspecific epitope data, and at the same time have identified critical knowledge gaps and highlighted potential areas for further research.…”
Section: Introductionmentioning
confidence: 98%
“…By conducting a comprehensive meta-analysis of available data for Plasmodium immune epitopes, Vaughan et al have identified more than 5,000 unique B-cell and T-cell epitopes for malaria parasites (60). Several of the P. falciparum and P. vivax epitopes were identified in extensive field studies conducted over the last 2 decades (12,23,35,57) and by computer-based predictions of immune epitopes by analysis of genomic and proteomic databases; some of these predictions were validated in HLA-peptide binding studies and in vitro immunological studies (4,(11)(12)(13)29).…”
mentioning
confidence: 99%